2020
DOI: 10.3389/fcimb.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Nocardia by Next-Generation Sequencing

Abstract: In this original study, we retrospectively reviewed the cases of nocardiosis diagnosed through culture and next-generation sequencing (NGS) methods between 2014 and 2018 in Huashan Hospital and found out that the latter way can not only improve the detection rate of Nocardia spp. but also greatly reduce the turnaround time. In addition, by comparing nocardiosis and non-nocardiosis patients both of whose samples had Nocardia spp. detected by NGS, we found that Nocardia's specific reads ranking among top two mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…More than 50 species can cause infections both in immunocompetent and immunocompromised individuals [ 4 ]. Due to the inexperience of the clinical laboratory technicians in primary hospitals in China, the particular characteristics of Nocardia growth, the unspecific pulmonary symptoms, as well as the low sensitivity of the culture-based method for diagnosis of nocardiosis [ 5 7 ], it is easy to miss detection of Nocardia in clinical practice. Partially, as a result, Nocardia infection is underestimated in China.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 species can cause infections both in immunocompetent and immunocompromised individuals [ 4 ]. Due to the inexperience of the clinical laboratory technicians in primary hospitals in China, the particular characteristics of Nocardia growth, the unspecific pulmonary symptoms, as well as the low sensitivity of the culture-based method for diagnosis of nocardiosis [ 5 7 ], it is easy to miss detection of Nocardia in clinical practice. Partially, as a result, Nocardia infection is underestimated in China.…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous retrospective study, 14 samples from the patients diagnosed with nocardiosis were tested by both mNGS and culture. All 14 samples were positive for Nocardia by mNGS, but only 5 samples had positive culture results [ 16 ]. Another research reported a brain abscess caused by Nocardia diagnosed by Ziehl–Neelsen stain and mNGS, while the blood culture was negative [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, isolation of Nocardia on common or selective media usually takes 2-7 days, which causes a delay in diagnosis 22,23 . Some Nocardia strains even need between 1-4 weeks to generate available results, because they require strict culture conditions and have a slow growth rate at 35°C in standard culture medium; the presence of normal ora or treatment with antimicrobial therapy would also affect Nocardia culture 11,13,14,24,25 . In our study, the average time for microbial detection was 4.8 days, and 11 specimens required more than 7 days, which exceeded the conventional culture time (≥ 2 days).…”
Section: Discussionmentioning
confidence: 99%